2021
DOI: 10.1093/rheumatology/keab021
|View full text |Cite
|
Sign up to set email alerts
|

Open-label phase 3 study of intravenous golimumab in patients with polyarticular juvenile idiopathic arthritis

Abstract: Objectives Assess efficacy, pharmacokinetics (PK), and safety of intravenous (IV) golimumab in patients with polyarticular-course juvenile idiopathic arthritis (pc-JIA). Methods Children aged 2 to < 18 years with active pc-JIA despite methotrexate therapy for ≥2 months received 80 mg/m2 golimumab at Weeks 0, 4, then every 8 weeks through week 52 plus methotrexate weekly through week 28. The primary and major secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The following response rates were recorded: ACR30 -84%, ACR50 -80%, ACR70 -70% and ACR90 -47% at week 28, being maintained until week 52. Golimumab was well tolerated and provided good clinical efficacy in children and adolescents with active polyarticular JIA 15 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The following response rates were recorded: ACR30 -84%, ACR50 -80%, ACR70 -70% and ACR90 -47% at week 28, being maintained until week 52. Golimumab was well tolerated and provided good clinical efficacy in children and adolescents with active polyarticular JIA 15 .…”
Section: Discussionmentioning
confidence: 94%
“…Numerous studies have shown the efficacy and safety of golimumab biological therapy in children with JIA 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, bDMARDs not approved for JIA are introduced into the treatment. 7,21 Several reports suggest the efficacy and safety of golimumab [22][23][24] and infliximab [25][26][27][28][29] for non-sJIA. These findings support the inclusion of the off-label use of bDMARDs in our study.…”
Section: Dovepressmentioning
confidence: 99%
“…Moreover, aside from its soluble form, as a transmembrane protein, TNFα on both Mφs and fibroblasts has been shown to induce arthritis in transgenic mice [ 95 ]. Currently, the success of treating JIA patients with various biologics interfering with TNFα signaling has confirmed the importance of TNFα in the pathogenesis of JIA [ 99 , 100 , 101 ].…”
Section: Effect Of Monocyte/macrophage-produced Cytokines and Chemokinesmentioning
confidence: 99%